Análise e melhoria de processos dos estágios em cursos do sistema de ensino naval : o caso da realização do estágio inicial em um navio da Marinha do Brasil - Machado, Thiago Muzi. (2019)
This dissertation explores the process of initial stage and application related to the course of Naval Education System, specifically in what concerns the difficulty to implement certain tasks assigned to military in training. As a central topic of this work, it will be discussed the specific dificulties to implement norms related to the practice and execution of obligations during military internship, as a matter of fact, it is relevant to report that there is a lot of effort to adapt to troubled routines of the vessel. The aim is to maximize the efficiency and quantity of taks performed by the trainees, taking in consideration what the Naval Education System interprets as necessary to capacitate its trainees and what would really contribuite to the routine and training during internship. The empirical study is carried out by ergonomic analysis in the a Navy Ship in Brazil, in order to understand the routine on board and the innumerable activies perfomed by the trainnees during internship, so that it would be possible to understand what the norms command and what is acctually done in practice. Given the results obtainted, it is possible to present some alternatives, in order to minimize the consequences of non perfomed tasks. So that, it would contribuite to improve the pratical application of theoretical concepts taught in the courses of the naval education system.